POPULATION ECOLOGY OF THE LITTLE CORMORANT, PHALACROCORAX NIGER IN A COLONY - Naher, Habibon; Sarker, N.J. (Ecoprint: An International Journal of Ecology, 2004)
Population ecology of the little cormorant (Phalacrocorax niger) was studied from February 2003 to March 2004. The study was performed at the village named Dhonagoda near the river Dhonagoda under the thana Matlab in the district of Chandpur. In the non breeding season, the little cormorant was found in Dhonagoda river, canal situated on the both sides of the Matlab-Dhonagoda embankment and in the ponds near the breeding site. In the breeding season they selected their nesting site in several trees of a house in its immediate vicinity of pond. They built their nests at Koroi (Albizzia procera), Mango (Mangifera indica), Fig (Ficus spp.), Siamese rough bush (Streblus asper), Coconut (Cocos nucifera). The little cormorant prepared nests in the trees, the height of which varied from 9.2 to 11.2 m and the breadth from 66 to 125 cm. Numerous nests (3 to31) were built in a single tree. The little cormorant collected dry pepper (Capsicum frutescens) twigs, dry leaves of Eucalyptus (Eucalyptus citriodora), fruits of Coriander (Coriandrum sativum), grass (Cynodon dactylon), dry stem of Indian Plum (Zizyphus jujuba), Marsh herb (Enhydra fluctuans), Jute (Corchorus olitorius), straw etc. as nesting materials. During the study period, 198 nests were recorded in the colony. In total, 718 eggs were laid. Among these 557 eggs were hatched and 408 nestling were fledged. In the study period, it was recorded that 124 (83.22%) nestling were stolen by the local boys.Key words: Population, ecology, little cormorant (Phalacrocorax niger), colony, Bangladesh. Ecoprint Vol.11(1) 2004.